Significado del trabajo para las vendedoras ambulantes de la Avenida Central de San José - Valerín Alvarado, Evelyn (2013)
This article presents an approach to the symbolic world that revolves around the work undertaken by street saleswomen in the Central Avenue in San José. It describes the characterizations that have been made “from the outside” about this economical sector while it contrasts what being a street saleswoman means for themselves, elucidating their own experiences, that is, showing a view “from the inside”.